Systematization and analysis of the offer of organic products at the Bom Pastor fair in Juiz de Fora, Minas Gerais - Pereira, Gabriel Barbosa (2022)
The emergence of the COVID-19 pandemic in the year 2020, which led to the need for social isolation, caused changes in food systems, as well as consumer relations. Therefore, the objective of this work consisted in the systematization and analysis of the offer of organic products at Feira do Bom Pastor, located in the municipality of Juiz de Fora - MG, during the pre and post pandemic period of COVID-19. Data from the fair and MOGICO online baskets were collected from January 2019 to May 2021. In 2021, there were a total of eight fairgrounds and 15 stalls, as there are marketers who have up to four stalls to market their products. products. It is worth noting that there is a uniformity in the offer of products in the period studied, as among the 54 products offered, 31 are available throughout the year, with a variety of vegetables (fruits and vegetables). Before the COVID-19 pandemic, there was no collective marketing of organic products among marketers, in the form of baskets at home. As a result of COVID-19, which started in March 2020, the fairs were suspended and from then on, the fairs organized themselves in order to collectively market their products in the form of an online basket. The creation of the website for commercialization provided producers with a new way to sell their products amid the continuity of the COVID-19 pandemic, in addition to making them more hopeful and motivated to improve organic production planning.